A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae) - Campos, Martha R.; Lasso, Carlos A.; Arias, Maribel (Zootaxa, 2019)
A new species of Phallangothelphusa Pretzmann, 1965, is described from the foothills of the Serranía Yariguíes, Santander Department, Magdalena river basin, Colombia. The number of the species increases to five: P. dispar (Zimmer, 1912), P. magdalenensis Campos, 1998, P. juansei Campos, 2010, P. martensis Cardona & Campos, 2012, and P. tangerina n. sp. The new species is distinguished from its congeners mainly by the morphology of the first male gonopod, particularly by the shapes of the mesial and lateral processes, and the surface and outline form of the apex.